Implementasi Pendidikan Karakter Melalui Budaya Sekolah di SMP Shafiyyatul Amaliyyah Medan - Dairina Yusri; Nanda Nurul Baiti; Wahyu Pertiwi Batu Bara; Fikry Chairanda; Fahri Azizi (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
This study aims to describe the implementation of character education through school culture at SMP Shafiyyatul Amaliyah Medan. The data of this research can be obtained through the results of interviews, observations and documentation. This research itself basically provides some information that school culture has a big influence on the formation of student characters. A good school culture will give birth to good character in these students. some positive activities can be a strategy in implementing student characters through school culture. Teachers and students must work together in synergy to create good characters for the students themselves